Legal Protection for Child Offenders in Conflict with the Law at the West Java High Prosecutor’s Office: A Quantitative Study Based on 2022–2024 Case Data - Sabar, Sabar; Iryana, Anri; William Alphazandra, Arvin; Ahmad Jamaludin (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2026)
Children in conflict with the law constitute a vulnerable group that requires special legal treatment to safeguard their rights and mitigate the adverse effects of criminal proceedings on their physical, psychological, and social development. In Indonesia, this protection is primarily governed by Law Number 11 of 2012 on the Juvenile Criminal Justice System, which prioritizes restorative justice and diversion as the main approaches for resolving juvenile cases. This study examines the regulatory framework, implementation, and effectiveness of legal protection for children in conflict with the law, with particular attention to the application of restorative justice and diversion and the fulfillment of children’s rights at each stage of the criminal justice process. The research employs a normative juridical approach, supported by empirical case data from the West Java High Prosecutor’s Office covering 2022–2024 (n = 788), with cases predominantly involving boys. The findings indicate that although the existing legal framework provides relatively comprehensive safeguards, implementation remains suboptimal due to inconsistent application of norms, weak inter-agency coordination, and limited social support for rehabilitation and reintegration. Strengthening institutional coordination, improving procedural compliance, and expanding community-based support are therefore essential to enhance the effectiveness of child protection within the juvenile justice system.